Information management in health systems: Considering an organic approach - Knight, Shirlee-ann (2011)
The 2009 Report by the National Health and Hospitals Reform Commission (NHHRC) to the Federal government described the Australian Health Sector (AHS) and its information processes as fragmented. When presented with the observation that an organisation and its information or management processes are fragmented, it seems natural to assume such a state to be deficient. More often than not, the response is for an organisation to attempt to reform or standardise its systems in an attempt to un-fragment their core business. This paper argues for an alternative paradigm, informed by the science of Complexity, which conceptualises complex organisations and their processes in terms of being Complex Adaptive Systems (CAS). In this context, traditional information and management science approaches to understanding organisational characteristics such as fragmentation, process and information duplication or redundancy, and system regulation may require a rethink.